Phenomic selection in slash pine multi-temporally using UAV-multispectral imagery - Li, Yanjie; Yang, Xinyu; Tong, Long; Wang, Lingling; Xue, Liang; Luan, Qifu; Jiang, Jingmin (Frontiers in Plant Science, 2023)
Genomic selection (GS) is an option for plant domestication that offers high efficiency in improving genetics. However, GS is often not feasible for long-lived tree species with large and complex genomes. In this paper, we investigated UAV multispectral imagery in time series to evaluate genetic variation in tree growth and developed a new predictive approach that is independent of sequencing or pedigrees based on 2 multispectral imagery plus vegetation indices (VIs) for slash pine. Results show that temporal factors have a strong influence on the h 2 of tree growth traits. High genetic correlations were found in most months, and genetic gain also showed a slight influence on the time series. Using a consistent ranking of family breeding values, optimal slash pine families were selected, obtaining a promising and reliable predictive ability based on multispectral+VIs (MV) alone or on the combination of pedigree and MV. The highest predictive value, ranging from 0.52 to 0.56, was found in July. The methods described in this paper provide new approaches for phenotypic selection (PS) using high-throughput multispectral unmanned aerial vehicle (UAV) technology, which could potentially be used to reduce the generation time for conifer species and increase the genetic granularity independent of sequencing or pedigrees.